Characterisation of the inflammatory cytokine and growth factor profile in a rabbit model of proliferative vitreoretinopathy - Wong, Chee Wai (2020)
To clarify the mechanisms and their temporal relationship in the development of proliferative vitreoretinopathy (PVR), we measured vitreous levels of pro-inflammatory cytokines and growth factors in a rabbit model of PVR. PVR was surgically induced in 11 rabbit eyes by vitrectomy, retinotomy, cryotherapy and injection of platelet-rich plasma at baseline. Severity of PVR was assessed on dilated fundal examination with indirect binocular ophthalmoscopy and graded based on the revised experimental PVR classification. Severe PVR was defined as stage 5 or worse. Vitreous concentrations of interleukin 6 (IL-6), interleukin 8 (IL-8), interleukin 1 beta (IL-1 β), tumor necrosis factor beta (TNF-β), granulocyte macrophage colony stimulating factor (GM-CSF), interferon gamma (IFN-γ), C reactive protein; (CRP), placental growth factor (PlGF), platelet derived growth factor BB (PDGF-BB), vascular endothelial growth factor (VEGF) and angiopoietin 2 (Ang-2) at weeks 2, 3 and 4 were compared to baseline and correlations between the cytokines with PVR severity were assessed. Four weeks after PVR induction, 5 eyes (45.5%) had developed severe PVR. IL-8 was raised at 2 weeks post PVR induction (1.46 ± 0.48 pg/ml vs 0.53 ± 0.25 pg/ml, p = 0.04) and remained significantly elevated at week 4 (2.6 ± 3.1 pg/ml, p = 0.03). CRP was significantly raised at week 4 (34.8 ± 12.0 pg/ml vs 13.0 ± 13.1 pg/ml, p < 0.001). Among the growth factors, PDGF-BB was the earliest to show significantly elevated levels, at 3 weeks (50.4 ± 19.0 pg/ml vs 6.2 ± 10.1 pg/ml) and remained elevated at week 4 (p = 0.002), while PlGF (11.2 ± 7.7 pg/ml vs 5.3 ± 3.8 pg/ml, p = 0.002) and Ang2 (13617.0 ± 8170.2 pg/ml vs 38593.8 ± 8313.4, p = 0.02) were significantly raised at week 4. IFN-γ (p = 0.03), PDGF-BB (p = 0.02) and VEGF (p = 0.02) were significantly associated with PVR severity. We demonstrated that inflammatory cytokines IL-6, -8, elevation post PVR induction is followed by elevated levels of fibroproliferative growth factors, Ang2, PlGF, VEGF and PDGF-BB in the development of PVR. These findings will guide future studies targeting appropriate therapeutic strategies for the treatment of PVR.